Carrot (Daucus carota L . ssp. sativus (Hoffm.) Arcang.) as source of antioxidants - Judita BYSTRICKÁ; Petra KAVALCOVÁ; Janette MUSILOVÁ; Alena VOLLMANNOVÁ; Tomáš TÓTH; Marianna LENKOVÁ (Acta Agriculturae Slovenica)
Carrot (Daucus carota L. s sp. sativus (Hoffm.) Arcang.) is a significant source of vitamins (A, B, C) and beta carotene. Further it contains vitamins B, C, E, H, folic acid and pantothenic acid. Carrot is an important source of trace elements (K, Na, Ca, Mg, P, S, Mn, Fe, Cu and Zn). Consumption of carrot improves eyesight, lowers cholesterol and improves digestion. In this work we evaluated and compared content of total polyphenols, ß-caroteneand antioxidant activity in five varieties of carrot (’Jitka’, Kardila’, Katlen , Rubína’ and Koloseum) Samples of carrot were collected at full maturity stages from area of Bardejov. Samples of fresh carrot were homogenized (25 g) in 50 ml 80 % ethanol and analysed after sixteen hours. The content of the total polyphenols was determined by using the Folin-Ciocalteu reagent (FCR). The content of ß-carotene was determined spectrophotometricaly at 450 nm. Antioxidant activity was measured using a compound DPPH (2.2-diphenyl-1-picrylhydrazyl) at 515.6 nm using spectrophotometer. Total polyphenols content in samples ranged from 81.25 ± 13.11 mg/kg to 113.69 ± 11.57 mg/kg and content of ß-carotenes ranged from 24.58 ± 2.38 mg/kg to 124.28 ± 3.54 mg/kg. We also evaluated and compared the antioxidant activity in selected varieties of ca rrot, which varied from 6.88 ± 0.92 % to 9.83 ± 0.62 %. Statistically si gnificant the highest value of total polyphenols was recorded in variety of Koloseum (113.69 ± 11.57 mg/kg). This variety is also character ized by the highest content of ß- carotene (124.28 ± 3.54 mg/kg) as well as the highest value of antioxidant activity (9.83 ± 0.62 %).